PENGARUH PENAMBAHAN AIR KELAPA DAN BERBAGAI KONSENTRASI HORMON 2,4-D PADA MEDIUM MS DALAM MENGINDUKSI KALUS TANAMAN ANGGUR HIJAU (VITIS VINIFERA L.) - Dwi PYD, Niluh Made; Waeniati, Waeniati; Muslimin, Muslimin; Suwastika, I Nengah (Univ. Tadulako, 2012)
Green grape (Vitis vinifera L.) is popular cultivar of grape that produce valuable of table fruit whic usually grown via vegetative propagation. Another chalanging tecnology in grape propagate is by induction of callus in tissue culture tecnique. The study on grape callus induction was done at Tissue Culture Laboratory-Forestry Faculty-Tadulako University Palu, during periode of January 2012 until May 2012. This experiment was arranged in completely randomized design with 3 different mediums as treatments and 3 replications. The treatments were MS0 + 2,4-D 0.5 ppm + 10% coconut water (D1), MS0 + 2,4-D 1 ppm + 10% coconut water (D2), dan MS0 + 2,4-D 1.5 ppm + 10% coconut water (D3). The observed parameters in this research were the days appear of callus, percentage of explant producing callus (%), also observation on morphology and the cell of callus. The result showed that the MS medium with 10% coconut water and 2.4-D could induce the callus of the green grape and the best medium was MS0 + 2.4-D 1.5 ppm + 10% coconut water (D3). It was shown by responding in emerging of callus in 11 days after induction, the percentage of explant producing callus was 76.67%. Produced callus was active in cell proliferation, and it has a compac texture, with brown-greeny color of callii.